HUMOR DALAM PENDIDIKAN ISLAM ANAK: STUDI ETNOPEDAGOGI GURU MI DALAM MENANAMKAN NILAI-NILAI KEISLAMAN - Kurnia, Asraf; Rosyada, Dede; Zalnur, Muhammad; Matanari, Thamara Putriani Br; Hendrizal, Hendrizal (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Humor holds significant potential in fostering humanistic and joyful learning, particularly in the context of Islamic Religious Education (PAI) at the madrasah ibtidaiyah level. This article aims to examine the role of humor as a pedagogical strategy in instilling Islamic values in children through an ethnopedagogical approach. The study employs a library research method by reviewing relevant literature on educational humor, Islamic education for children, and culturally grounded teaching strategies. The findings reveal that verbal, nonverbal, and culturally based humor can effectively enhance students’ understanding of moral, ethical, and ritual values in Islam. Humor also contributes to creating a positive classroom climate, improving student engagement, and bridging religious concepts with children's everyday experiences. From an ethnopedagogical perspective, humor reflects local wisdom that enriches Islamic educational practices and strengthens cultural affinity. However, the use of humor demands ethical sensitivity and strong communication skills from teachers. Therefore, training in culturally responsive and ethical humor use is recommended for Islamic education teachers. This study offers a conceptual contribution to developing a more contextual, affective, and culturally rooted approach to Islamic education in elementary settings.